Preparation method of high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth

By using a high-abundance rare earth preparation method and micronization and post-processing techniques, the coercivity and corrosion resistance of NdFeB magnets are improved, solving the stability and reliability problems of NdFeB magnets in high-temperature and harsh environments and extending their service life.

CN121034787AInactive Publication Date: 2025-11-28HUNAN BENLANG NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511573768.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2025-11-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The low coercivity of neodymium iron boron magnets leads to a decay in magnetic properties under high temperature environments and reverse magnetic fields, affecting their stability and reliability under dynamic working conditions.

Method used

A preparation method containing high abundance of rare earth elements is adopted. Tungsten disulfide in the micro powder is added as a carrier to form a colloidal solution with oleylamine and octadecene. The nano-sized micro powder is ultrasonically and thermally treated. Dysprosium trifluoride replaces neodymium in the neodymium-iron-boron main phase during sintering to form a dysprosium-rich shell, which improves the magnetocrystalline anisotropy. Sodium molybdate and cerium nitrate are used in the post-treatment to form a dense oxide film, which provides self-healing capability.

Benefits of technology

It effectively enhances the coercivity of neodymium iron boron magnets and extends their service life in salt spray and humid heat environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121034787A_ABST
    Figure CN121034787A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of neodymium-iron-boron magnets, in particular to a preparation method of a high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth, and the preparation method comprises the following steps: S1, preparing alloy powder; s2, micro powder preparation; s3, preparing mixed powder; s4, molding preparation; and S5, post-processing. According to the preparation method, the micro powder is added, the tungsten disulfide can be used as a carrier in the preparation of the micro powder, the lubricating property of the tungsten disulfide is beneficial to reducing powder agglomeration and improving the uniformity of the material in the mixing process, a uniform colloidal solution can be formed through treatment of oleylamine and octadecene, and the tungsten disulfide is nanocrystallized through ultrasonic and heat treatment; according to the preparation method, the specific surface area is increased, mixing with other components is facilitated, the activity of the micro powder is enhanced, dysprosium trifluoride is decomposed in the sintering process of dysprosium trifluoride, so that dysprosium atoms replace neodymium in a neodymium-iron-boron main phase, magnetocrystalline anisotropy is improved, the demagnetization resistance of a magnet is effectively improved, and the purpose of improving the coercive force is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of neodymium-iron-boron magnets, in particular to a preparation method of a high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth. BACKGROUND

[0002] The neodymium-iron-boron magnet is a kind of artificial permanent magnet, has the characteristics of high cost performance, small size, light weight, good mechanical properties and strong magnetism, and is widely applied in the fields of electric vehicles, hybrid electric vehicles, wind power generation, variable frequency air conditioners, medical equipment, elevators, sound equipment and mineral separation.

[0003] As a representative of modern high-performance permanent magnet materials, the neodymium-iron-boron magnet has excellent residual magnetism and magnetic energy product, but the low coercivity problem of the neodymium-iron-boron magnet seriously restricts the actual application. The weak electricity leads to that the magnet has insufficient ability to resist demagnetization when in a high-temperature environment or subjected to a reverse magnetic field, and the magnetic performance will irreversibly decay, thereby directly affecting the stability and reliability of the magnet under dynamic working conditions. Therefore, in order to solve the low coercivity problem of the neodymium-iron-boron magnet and improve the ability of the neodymium-iron-boron magnet to resist demagnetization, the application provides the preparation method of the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth. SUMMARY

[0004] The application aims to provide the preparation method of the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth. The high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth prepared by the application can effectively improve the ability of the magnet to resist demagnetization, thereby achieving the purpose of improving the coercivity, and can significantly prolong the service life of the magnet in a harsh environment such as salt spray and heat.

[0005] To achieve the above-mentioned purpose, the application provides the following technical scheme: a preparation method of a high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth, comprising the following steps: S1: alloy powder preparation, the alloy powder comprises neodymium-iron-boron powder, cerium-iron alloy powder, copper-gallium alloy powder and magnesium oxide powder, and the weight percentage is as follows: 2-4% of the magnesium oxide powder, 2-4% of the copper-gallium alloy powder, 4-6% of the cerium-iron alloy powder, and the balance is supplemented by the neodymium-iron-boron powder to 100%; S2: micro powder preparation, the mass of the micro powder is 0.4-0.6% of the mass of the alloy powder; S3: mixed powder preparation, the alloy powder is mixed with the micro powder to prepare the mixed powder; S4: forming preparation, the mixed powder is sequentially subjected to pressing treatment, sintering treatment and tempering treatment to prepare the magnet; S5: post-treatment, the magnet is subjected to post-treatment to prepare the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth.

[0006] Further, the mass ratio of neodymium, iron and boron in the neodymium-iron-boron powder is 1:(7-8):(0.4-0.6), the mass ratio of cerium and iron in the cerium-iron alloy powder is 1:2, and the mass ratio of copper and gallium in the copper-gallium alloy powder is 1:(0.2-0.4).

[0007] Further, the method for preparing the alloy powder is as follows: the neodymium-iron-boron powder, the cerium-iron alloy powder, the copper-gallium alloy powder and the magnesium oxide powder are added into a mixer, the mixer is set to stir at 200-400 rpm for 40-60 min, and the obtained product is added into a ball mill for ball milling treatment, the ball milling treatment time is 8-10 h, and the rotation speed is 200-300 rpm, so as to obtain the alloy powder.

[0008] Further, the method for preparing the micro powder is as follows: the tungsten disulfide, the oleylamine and the octadecene are added into a flask and mixed, and then the obtained product is added into an ultrasonic cleaner for ultrasonic treatment for 20-30 min, the obtained product is added into a reaction kettle, the reaction kettle is set to heat to 120-130 ℃ under a nitrogen atmosphere, the stirring speed is set to 60-80 rpm, and the obtained product is stirred at constant temperature for 20-30 min, then the stirring is stopped, the reaction kettle is set to heat to 260-280 ℃, and the obtained product is heated for 40-50 min, the obtained product is added into a centrifugal machine, the centrifugal machine is set to centrifugal treatment at 8000-10000 rpm for 6-10 min, the solid obtained by centrifugal treatment is washed with ethanol and deionized water alternately for 3-5 times, the obtained product is added into an oven, the oven is set to dry treatment at 60-80 ℃ for 3-5 h, so as to obtain a mixed powder, the mixed powder, the dysprosium trifluoride and the nickel powder are added into a mixer, the mixer is set to stir at 600-800 rpm for 40-60 min, so as to obtain the micro powder.

[0009] Further, the mass ratio of the tungsten disulfide, the oleylamine and the octadecene is 1:(8-10):(4-6), and the mass ratio of the mixed powder, the dysprosium trifluoride and the nickel powder is 1:(0.6-0.8):(0.4-0.6).

[0010] Further, the method for preparing the mixed powder material is as follows: the alloy powder and the micro powder are added into a mixer, anhydrous ethanol is added into the mixer, and the mixture is mixed at 40-60 rpm for 2-4 h, and the obtained product is added into a vacuum drying box and dried at 50-60 ℃ for 2-4 h, so as to obtain the mixed powder material.

[0011] Further, the addition amount of the anhydrous ethanol is 0.2-0.4% of the mass of the alloy powder.

[0012] Further, the forming preparation method is that: the powder material is mixed and formed under a magnetic field of 1.5T, the pressure is 600MPa, a blank is obtained, the blank is sent into a sintering furnace, the sintering temperature is set to be 1020-1100 DEG C, the time is 2h, then the temperature is decreased to 800-860 DEG C, the temperature is kept for 4-6h, the obtained product is cooled to normal temperature, then the temperature is increased to 500-580 DEG C, the temperature is kept for 3-4h, the tempering treatment is completed after the product is cooled to normal temperature, and the magnet is prepared.

[0013] Further, the post-treatment method is that: the magnet is subjected to cleaning treatment and drying, then is soaked in a treatment liquid for 10-20min, the magnet after soaking is placed in an oven, the oven is set to be 80-100 DEG C for drying treatment for 20-40min, the post-treatment is completed, and the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth is prepared.

[0014] Further, the treatment liquid is prepared by mixing cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water, and the mass ratio of cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water is 1:(0.2-0.4):(0.06-0.08):(0.4-0.6):(100-150).

[0015] Compared with the prior art, the present application has the following beneficial effects: 1. In the preparation of the neodymium-iron-boron magnet, the micro powder is added, the tungsten disulfide is used as a layered material and as a carrier in the preparation of the micro powder, the lubricity of the tungsten disulfide helps to reduce powder agglomeration in the mixing process and improve the uniformity of the material, the treatment of the oil amine and octadecene can form a uniform colloidal solution, the ultrasonic and heat treatment can nanoize the tungsten disulfide, increase the specific surface area, facilitate the mixing with other components, and enhance the activity of the micro powder, the dysprosium trifluoride is decomposed in the sintering process, dysprosium atoms replace neodymium in the main phase of the neodymium-iron-boron, the magnetic crystal anisotropy is improved, and the ability of the magnet to resist demagnetization is effectively improved, so that the coercivity is improved.

[0016] 2. In the soaking treatment in the post-treatment, the molybdate ions provided by the sodium molybdate can react with metal ions such as iron and neodymium on the surface of the magnet to form a dense and strongly adhered composite oxide film, so as to isolate the corrosion medium such as chloride ions and moisture, the cerium ions released by the cerium nitrate are deposited at the micro defects or active points on the surface of the magnet to form stable and insoluble cerium compounds, so as to physically block the corrosion channel, and when the protective film is locally damaged due to mechanical damage or the like, the soluble Ce 3+ in the film layer and the adjacent area can be dissolved and migrated to the damage again to form a new protective layer, so that a certain self-repairing ability is provided, and the service life of the magnet in a harsh environment such as salt spray and humid heat is significantly prolonged. Attached Figure Description

[0017] Figure 1 The present invention provides a flowchart of a method for preparing a high-coercivity neodymium iron boron magnet containing high abundance of rare earth elements. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] It should be noted that the raw materials used in the following embodiments are all commercially available.

[0020] Example 1: In a first aspect, a method for preparing a highly coercive neodymium iron boron magnet containing high abundance of rare earth elements includes the following steps: S1: Alloy powder preparation, the alloy powder includes neodymium iron boron powder, cerium iron alloy powder, copper gallium alloy powder, and magnesium oxide powder, by weight percentage: 2% magnesium oxide powder, 2% copper gallium alloy powder, 4% cerium iron alloy powder, and the balance is supplemented by neodymium iron boron powder to 100%; The method for preparing the alloy powder is as follows: neodymium iron boron powder, cerium iron alloy powder, copper gallium alloy powder, and magnesium oxide powder are added to a mixer, which is set to 200 rpm for 40 minutes. The resulting product is then added to a ball mill for ball milling for 8 hours at a speed of 200 rpm to obtain the alloy powder.

[0021] S2: Micropowder preparation, the mass of the micropowder is 0.4% of the mass of the alloy powder; The method for preparing the micro powder is as follows: tungsten disulfide, oleylamine, and octadecene are mixed in a flask and ultrasonically treated in an ultrasonic cleaner for 20 minutes. The resulting product is added to a reaction vessel and heated to 120°C under a nitrogen atmosphere. The stirring speed is set to 60 rpm and the mixture is stirred at a constant temperature for 20 minutes. After stirring is stopped, the reaction vessel is heated to 260°C and held for 40 minutes. The resulting product is added to a centrifuge and centrifuged at 8000 rpm for 6 minutes. The solid is obtained by centrifugation and washed three times alternately with ethanol and deionized water. The resulting product is added to an oven and dried at 60°C for 3 hours to obtain a mixed powder. The mixed powder, dysprosium trifluoride, and nickel powder are added to a mixer and stirred at 600 rpm for 40 minutes to obtain the micro powder. S3: mixed powder preparation, alloy powder and micro powder are mixed to prepare mixed powder; S4: forming preparation, the mixed powder is sequentially subjected to pressing treatment, sintering treatment and tempering treatment to prepare the magnet; The forming preparation method is that the mixed powder is pressed and formed under a magnetic field of 1.5 T at a pressure of 600 MPa to obtain a blank, the blank is sent into a sintering furnace, the sintering temperature is set to 1020 DEG C, the time is 2 h, then the temperature is lowered to 800 DEG C, the temperature is kept for 4 h, the obtained product is cooled to room temperature, then the temperature is raised to 500 DEG C, the temperature is kept for 3 h, the product is cooled to room temperature, the tempering treatment is completed, and the magnet is prepared.

[0022] S5: post-treatment, the magnet is subjected to post-treatment to prepare the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth; The post-treatment method is that the magnet is subjected to cleaning treatment and drying, then is soaked in a treatment liquid for 10 min, the magnet after soaking is placed in an oven, the oven is set to 80 DEG C for drying treatment for 20 min, the post-treatment is completed, and the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth is prepared. The treatment liquid is prepared by mixing cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water.

[0023] On the other hand, the mass ratio of neodymium, iron and boron in the neodymium-iron-boron powder is 1:7:0.4, the mass ratio of cerium and iron in the cerium-iron alloy powder is 1:2, and the mass ratio of copper and gallium in the copper-gallium alloy powder is 1:0.2.

[0024] The mass ratio of tungsten disulfide, oleylamine and octadecene is 1:8:4, and the mass ratio of mixed powder, dysprosium trifluoride and nickel powder is 1:0.6:0.4.

[0025] The mixed powder preparation method is that the alloy powder and the micro powder are added into a mixer, anhydrous ethanol is added into the mixer, the mixing treatment is set to 40 rpm for 2 h, the obtained product is added into a vacuum drying box, and drying treatment is carried out at 50 DEG C for 2 h to prepare the mixed powder.

[0026] The addition amount of anhydrous ethanol is 0.2% of the mass of the alloy powder.

[0027] The mass ratio of cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water is 1:0.2:0.06:0.4:100.

[0028] Example 2: In a first aspect, a preparation method of a high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth includes the following steps: S1: alloy powder preparation, the alloy powder comprises neodymium iron boron powder, cerium iron alloy powder, copper gallium alloy powder, magnesium oxide powder, and the weight percentage is: 3% magnesium oxide powder, 3% copper gallium alloy powder, 5% cerium iron alloy powder, and the balance is supplemented by neodymium iron boron powder to 100%; The method for preparing the alloy powder is that the neodymium iron boron powder, the cerium iron alloy powder, the copper gallium alloy powder and the magnesium oxide powder are added into a mixer, the mixer is set to stir at 300 rpm for 50 min, the obtained product is added into a ball mill for ball milling treatment, the ball milling treatment time is 9 h, and the rotation speed is 250 rpm, so as to prepare the alloy powder.

[0029] S2: micro powder preparation, the mass of the micro powder is 0.5% of the mass of the alloy powder; The method for preparing the micro powder is that the tungsten disulfide, the oleylamine and the octadecene are added into a flask and mixed, and then are subjected to ultrasonic treatment in an ultrasonic cleaner for 25 min; the obtained product is added into a reaction kettle, and is subjected to constant temperature stirring treatment at 70 rpm for 25 min under a nitrogen atmosphere, then the stirring is stopped, the reaction kettle is set to be heated to 270 DEG C and kept for 45 min, the obtained product is added into a centrifugal machine, and is subjected to centrifugal treatment at 9000 rpm for 8 min, the solid obtained by the centrifugal treatment is washed with ethanol and deionized water alternately for 4 times, the obtained product is added into an oven, and is subjected to drying treatment at 70 DEG C for 4 h to obtain a mixed powder; the mixed powder, dysprosium trifluoride and nickel powder are added into a mixer, and the mixer is set to stir at 700 rpm for 50 min, so as to prepare the micro powder. S3: mixed powder preparation, the alloy powder and the micro powder are mixed to prepare a mixed powder; S4: forming preparation, the mixed powder is subjected to pressing treatment, sintering treatment and tempering treatment in sequence to prepare a magnet; The method for preparing the magnet is that the mixed powder is pressed and formed under a magnetic field of 1.5 T at a pressure of 600 MPa to obtain a blank, the blank is put into a sintering furnace, the sintering temperature is set to 1060 DEG C, and the time is set to 2 h, then the temperature is lowered to 830 DEG C, and the temperature is kept for 5 h, the obtained product is cooled to room temperature, then the temperature is raised to 540 DEG C, and the temperature is kept for 3.5 h, then the product is cooled to room temperature, the tempering treatment is completed, and the magnet is prepared.

[0030] S5: post-treatment, the magnet is subjected to post-treatment to prepare a high-coercivity neodymium iron boron magnet containing high-abundance rare earth; The method for the post-treatment is that the magnet is subjected to cleaning treatment and drying, then is soaked in a treatment liquid for 15 min, and then is subjected to drying treatment at 90 DEG C for 30 min in an oven after being taken out, so as to complete the post-treatment and prepare the high-coercivity neodymium iron boron magnet containing high-abundance rare earth; The processing liquid is prepared by mixing cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water.

[0031] In another aspect, the mass ratio of neodymium, iron and boron in the neodymium-iron-boron powder is 1:7.5:0.5, the mass ratio of cerium and iron in the cerium-iron alloy powder is 1:2, and the mass ratio of copper and gallium in the copper-gallium alloy powder is 1:0.3.

[0032] The mass ratio of tungsten disulfide, oleylamine and octadecene is 1:9:5, and the mass ratio of mixed powder, dysprosium trifluoride and nickel powder is 1:0.7:0.5.

[0033] The method for preparing the mixed powder is as follows: the alloy powder and the micro powder are added into a mixer, anhydrous ethanol is added into the mixer, and the mixer is set to mix for 3h at 50rpm, and the obtained product is dried in a vacuum drying oven at 55℃ for 3h to obtain the mixed powder.

[0034] The addition amount of anhydrous ethanol is 0.3% of the mass of the alloy powder.

[0035] The mass ratio of cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water is 1:0.3:0.07:0.5:125.

[0036] Example 3: In a first aspect, a method for preparing a high-coercivity neodymium-iron-boron magnet containing high-abundance rare earths includes the following steps: S1: alloy powder preparation, the alloy powder includes neodymium-iron-boron powder, cerium-iron alloy powder, copper-gallium alloy powder and magnesium oxide powder, and the weight percentage is as follows: 4% magnesium oxide powder, 4% copper-gallium alloy powder, 6% cerium-iron alloy powder, and the balance is supplemented by neodymium-iron-boron powder to 100%; The method for preparing the alloy powder is as follows: the neodymium-iron-boron powder, the cerium-iron alloy powder, the copper-gallium alloy powder and the magnesium oxide powder are added into a mixer, the mixer is set to stir for 60min at 400rpm, and the obtained product is added into a ball mill for ball milling treatment, the ball milling treatment time is 10h, and the rotation speed is 300rpm to obtain the alloy powder.

[0037] S2: micro powder preparation, the mass of the micro powder is 0.6% of the mass of the alloy powder. The method for preparing the micro powder is as follows: the tungsten disulfide, the oleylamine and the octadecene are added into a flask and mixed, and then are subjected to ultrasonic treatment in an ultrasonic cleaner for 30 min; the obtained product is added into a reaction kettle, and is subjected to constant temperature stirring treatment under a nitrogen atmosphere at 80 rpm for 30 min; then the stirring is stopped, the reaction kettle is set to 280 DEG C for heat preservation for 50 min; the obtained product is added into a centrifugal machine, and is subjected to centrifugal treatment at 10,000 rpm for 10 min; the solid obtained by the centrifugal treatment is washed with ethanol and deionized water alternately for 4 times; the obtained product is added into an oven, and is subjected to drying treatment at 70 DEG C for 4 h to obtain a mixed powder; the mixed powder, dysprosium trifluoride and nickel powder are added into a mixer, and are subjected to stirring treatment at 700 rpm for 50 min to obtain the micro powder. S3: mixed powder preparation, the alloy powder and the micro powder are subjected to mixing treatment to obtain a mixed powder; S4: forming preparation, the mixed powder is subjected to pressing treatment, sintering treatment and tempering treatment in sequence to obtain the magnet; The method for forming preparation is as follows: the mixed powder is subjected to pressing forming under a magnetic field of 1.5 T at a pressure of 600 MPa to obtain a blank; the blank is fed into a sintering furnace, and is set to a sintering temperature of 1,100 DEG C for 2 h; then the temperature is lowered to 860 DEG C for heat preservation for 6 h; the obtained product is cooled to room temperature, and is then heated to 580 DEG C for heat preservation for 4 h; after being cooled to room temperature, the tempering treatment is completed to obtain the magnet.

[0038] S5: post-treatment, the magnet is subjected to post-treatment to obtain the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth; The method for post-treatment is as follows: the magnet is subjected to cleaning treatment and drying treatment, and then is soaked in a treatment liquid for 20 min; the magnet after soaking is placed in an oven, and is subjected to drying treatment at 100 DEG C for 40 min to complete the post-treatment to obtain the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth; The treatment liquid is prepared by mixing cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water.

[0039] On the other hand, the mass ratio of neodymium, iron and boron in the neodymium-iron-boron powder is 1:8:0.6, the mass ratio of cerium and iron in the cerium-iron alloy powder is 1:2, and the mass ratio of copper and gallium in the copper-gallium alloy powder is 1:0.4.

[0040] The mass ratio of the tungsten disulfide, the oleylamine and the octadecene is 1:10:6, and the mass ratio of the mixed powder, dysprosium trifluoride and nickel powder is 1:0.8:0.6.

[0041] The method for preparing the mixed powder is as follows: the alloy powder and the micro powder are added into a mixer, anhydrous ethanol is added into the mixer, and the mixer is set to mix for 4 h at 60 rpm. The obtained product is dried in a vacuum drying box at 60 °C for 4 h to obtain the mixed powder.

[0042] The addition amount of the anhydrous ethanol is 0.4% of the mass of the alloy powder.

[0043] The mass ratio of cerium nitrate, sodium molybdate, KH550, phosphoric acid and deionized water is 1:0.4:0.08:0.6:150.

[0044] Comparative Example 1, the difference between the comparative example and Example 1 is that the comparative example does not contain micro powder.

[0045] Comparative Example 2, the difference between the comparative example and Example 1 is that the comparative example uses dysprosium oxide powder with a purity of ≥99% and a particle size of 50 nm instead of micro powder.

[0046] Comparative Example 3, the difference between the comparative example and Example 1 is that the comparative example does not contain the treatment liquid.

[0047] Performance test: neodymium-iron-boron magnets prepared by the preparation methods of Examples 1-3 and Comparative Examples 1-3 are tested by making them into 10 mm x 10 mm x 5 mm cuboid samples; Magnetic property test: the standard of GB / T3217-2013 "Permanent (hard) magnetic material magnetic test method" is used to measure the residual magnetism, intrinsic coercive force, magnetic induction coercive force and maximum magnetic energy product using a pulse magnetic field magnetometer. The sample is saturated and magnetized before testing, and the environmental temperature is controlled at 25 °C. The obtained data is recorded in Table 1. Residual magnetism: unit Tesla (T), refers to the magnetic induction intensity remaining after the magnetic field is removed after the magnet is magnetized, which reflects the ability of the magnet to provide magnetic flux. The higher it is, the stronger the magnet may be; Intrinsic coercive force: unit kiloampere per meter (kA / m), is the reverse magnetic field strength required to reduce the magnetization intensity of the magnet to zero, which directly reflects the ability of the magnet to resist complete demagnetization. The higher the value, the better the temperature stability and service life of the magnet usually are; Magnetic induction coercive force: unit kiloampere per meter (kA / m), is the reverse magnetic field strength required to reduce the magnetic induction intensity of the magnet to zero, which reflects the stability of the magnet in the external dynamic magnetic circuit; Maximum magnetic energy product: unit kilojoule per cubic meter It is the maximum value of the magnetic energy product (B x H) on the demagnetization curve, which represents the maximum magnetic energy that the magnet can store, and is a key indicator for measuring the comprehensive performance of the magnet. The higher the value, the smaller the volume of the magnet required to produce the same magnetic force usually.

[0048] Corrosion resistance test: According to GB / T10125-2021 "Artificial Atmosphere Corrosion Test Salt Spray Test" standard, neutral salt spray test was carried out, and the time (h) of red rust appearing was recorded. The obtained data is recorded in Table 2; Bending strength test: The three-point bending method (general material mechanics standard) was used to measure the maximum stress before the sample broke, and the mechanical strength was evaluated. The bending strength (MPa) was recorded in Table 2.

[0049] Table 1:

[0050] By analyzing and comparing the data in Table 1, it can be seen that the remanence, intrinsic coercive force, magnetic induction coercive force, and maximum magnetic energy product of the neodymium-iron-boron magnets prepared by the preparation methods of Examples 1-3 are all better than those of Comparative Examples 1-3. Among them, the intrinsic coercive force and magnetic induction coercive force of Comparative Example 1 are greatly reduced after the micro powder is missing. This is because dysprosium trifluoride in the micro powder is the key source of grain boundary diffusion. After decomposition during sintering, dysprosium atoms will diffuse to form a dysprosium-rich shell, enhancing the magnetic crystal anisotropy field and hindering the nucleation of the reverse magnetization domain. The magnetic energy product and remanence decrease because the tungsten disulfide in the micro powder acts as a nano carrier, helping the liquid phase formed by the copper-gallium alloy to be more uniformly distributed, promoting sintering densification. After the micro powder is missing, the degree of densification decreases, the porosity increases, and the magnetic flux conduction efficiency decreases, resulting in a decrease in performance. The coercive force improvement effect of Comparative Example 2 is limited compared to Comparative Example 1. This is mainly because the traditional dysprosium oxide powder directly added is prone to agglomeration and has low diffusion efficiency, only partially penetrating the grain boundary, and cannot be uniformly dispersed and deeply diffused like the micro powder through the tungsten disulfide carrier. Therefore, the dysprosium-rich shell formed is incomplete, and the coercive force improvement is still far lower than that of Examples 1-3. The slight decrease in remanence and magnetic energy product is because the coarse particles of dysprosium oxide can cause local main phase dilution, thereby affecting the magnetic polarization strength to some extent. The data of Comparative Example 3, which lacks the treatment liquid, is close to that of Examples 1-3. This is because the treatment liquid is mainly used for surface post-treatment, affecting corrosion resistance, but has little effect on the bulk magnetic properties of the sintered magnet.

[0051] Table 2:

[0052] By analyzing and comparing the data in Table 1, it can be seen that the corrosion resistance and bending strength of the neodymium-iron-boron magnets prepared by the preparation methods of Examples 1-3 are all better than those of Comparative Examples 1-3. Among them, the corrosion resistance and mechanical strength of Comparative Example 1 are weakened, indicating that the active ingredients in the micro powder help to optimize the continuity of the grain boundary phase. After the micro powder is missing, defects and pores exist in the grain boundary, becoming a corrosion channel and a mechanical weak point, causing a decrease in performance. The corrosion resistance of Comparative Example 2 decreases because dysprosium itself does not participate in forming a dense protective film, but its addition has a slight filling effect on the grain boundary, so the corrosion resistance is better than that of Comparative Example 1 but not as good as that of the embodiment; Comparative Example 3 has a significant decrease in corrosion resistance due to the absence of the treatment liquid, because the treatment liquid is a surface treatment step performed after the magnet is sintered and tempered, and its main function is to form a protective film on the surface of the magnet through a chemical reaction, thereby improving corrosion resistance, and the absence of the treatment liquid will cause the corrosion resistance of the magnet to decrease significantly, so that the service life of the magnet will be significantly shortened when used in salt spray and other environments.

[0053] Through comparison and analysis of the relevant data in the table, it can be seen that the high-coercivity neodymium-iron-boron magnet containing high-abundance rare earth prepared by the application not only can effectively improve the ability of the magnet to resist demagnetization, thereby achieving the purpose of improving the coercivity, but also can significantly prolong the service life of the magnet in salt spray, humid heat and other harsh environments.

[0054] In the description of the present specification, the description of the terms "one embodiment", "example", "specific example" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0055] The preferred embodiments of the application disclosed above are only used to help explain the application. The preferred embodiments do not describe all the details and do not limit the application to the specific embodiments described. Obviously, many modifications and changes can be made according to the content of the present specification. The present specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the application, so that those skilled in the art can well understand and utilize the application. The application is limited only by the claims and their entire scope and equivalents.

Claims

1. A method for preparing a high-coercivity neodymium iron boron magnet containing high abundance of rare earth elements, characterized in that: Includes the following steps: S1: Alloy powder preparation, the alloy powder includes neodymium iron boron powder, cerium iron alloy powder, copper gallium alloy powder, and magnesium oxide powder, by weight percentage: 2-4% magnesium oxide powder, 2-4% copper gallium alloy powder, 4-6% cerium iron alloy powder, and the balance is supplemented by neodymium iron boron powder to 100%; S2: Micropowder preparation, the mass of the micropowder is 0.4-0.6% of the mass of the alloy powder; S3: Preparation of mixed powder: Alloy powder and micro powder are mixed to obtain mixed powder; S4: Molding and preparation, the mixed powder is pressed, sintered and tempered in sequence to obtain the magnet; S5: Post-processing, the magnet is post-processed to obtain a high coercivity neodymium iron boron magnet containing high abundance of rare earth elements.

2. The method for preparing a high-coercivity NdFeB magnet containing high rare earth abundance according to claim 1, characterized in that, The mass ratio of neodymium, iron and boron in neodymium iron boron powder is 1: (7-8): (0.4-0.6), the mass ratio of cerium and iron in cerium iron alloy powder is 1:2, and the mass ratio of copper and gallium in copper gallium alloy powder is 1: (0.2-0.4).

3. The method for preparing a high-coercivity NdFeB magnet containing high abundance of rare earth elements according to claim 1, characterized in that, The method for preparing the alloy powder is as follows: neodymium iron boron powder, cerium iron alloy powder, copper gallium alloy powder, and magnesium oxide powder are added to a mixer, and the mixer is set to 200-400 rpm for 40-60 minutes. The resulting product is then added to a ball mill for ball milling for 8-10 hours at a speed of 200-300 rpm to obtain the alloy powder.

4. The method for preparing a high-coercivity NdFeB magnet containing high rare earth abundance according to claim 1, characterized in that, The method for preparing the micro powder is as follows: tungsten disulfide, oleylamine, and octadecene are mixed in a flask and ultrasonically treated in an ultrasonic cleaner for 20-30 minutes. The resulting product is added to a reaction vessel and heated to 120-130°C under a nitrogen atmosphere. The stirring speed is set to 60-80 rpm, and the mixture is stirred at a constant temperature for 20-30 minutes. After stirring is stopped, the reaction vessel is heated to 260-280°C and held at that temperature for 40-50 minutes. The resulting product is added to a centrifuge and centrifuged at 8000-10000 rpm for 6-10 minutes to obtain a solid. The solid is washed alternately with ethanol and deionized water 3-5 times. The resulting product is added to an oven and dried at 60-80°C for 3-5 hours to obtain a mixed powder. The mixed powder, dysprosium trifluoride, and nickel powder are added to a mixer and stirred at 600-800 rpm for 40-60 minutes to obtain the micro powder.

5. The method for preparing a high-coercivity NdFeB magnet containing high rare earth abundance according to claim 4, characterized in that, The mass ratio of tungsten disulfide, oleylamine, and octadecene is 1:(8-10):(4-6), and the mass ratio of mixed powder, dysprosium trifluoride, and nickel powder is 1:(0.6-0.8):(0.4-0.6).

6. The method for preparing a high-coercivity NdFeB magnet containing high rare earth abundance according to claim 1, characterized in that, The method for preparing the mixed powder is as follows: alloy powder and micro powder are added to a mixer, anhydrous ethanol is added to the mixer, and the mixture is mixed at 40-60 rpm for 2-4 hours. The resulting product is then placed in a vacuum drying oven and dried at 50-60°C for 2-4 hours to obtain the mixed powder.

7. The method for preparing a high-coercivity NdFeB magnet containing high rare earth abundance according to claim 6, characterized in that, The amount of anhydrous ethanol added is 0.2 to 0.4% of the mass of the alloy powder.

8. The method for preparing a high-coercivity NdFeB magnet containing high rare earth abundance according to claim 1, characterized in that, The molding and preparation method is as follows: the mixed powder is pressed into shape under a magnetic field of 1.5T and a pressure of 600MPa to obtain a blank. The blank is sent into a sintering furnace and the sintering temperature is set to 1020-1100℃ for 2 hours. Then the temperature is lowered to 800-860℃ and held for 4-6 hours. After the product is cooled to room temperature, the temperature is raised to 500-580℃ and held for 3-4 hours. After cooling to room temperature, the tempering treatment is completed to obtain the magnet.

9. The method for preparing a high-coercivity NdFeB magnet containing high rare earth abundance according to claim 1, characterized in that, The post-processing method is as follows: the magnet is cleaned and dried, then soaked in a treatment solution for 10-20 minutes. After soaking, the magnet is placed in an oven and dried at 80-100℃ for 20-40 minutes. After the post-processing, a high coercivity neodymium iron boron magnet containing high abundance of rare earth elements is obtained.

10. The method for preparing a high-coercivity NdFeB magnet containing high abundance of rare earth elements according to claim 9, characterized in that, The treatment solution is prepared by mixing cerium nitrate, sodium molybdate, KH550, phosphoric acid, and deionized water, with the mass ratio of cerium nitrate, sodium molybdate, KH550, phosphoric acid, and deionized water being 1:(0.2-0.4):(0.06-0.08):(0.4-0.6):(100-150).

Citation Information

Patent Citations

  • Manufacture of near-net shaped rare-earth permanent magnet

    CN103035400A

  • Surface treatment method for permanent magnet material by adopting phosphorization agent to carry out phosphorization treatment

    CN103805983A

  • High-coercivity and high-temperature-resistant sintered neodymium-iron-boron magnet and preparation method thereof

    CN112086255A

  • Method of manufacturing a Rare Earth Sintering Magnet

    KR1020180004479A

  • Method of preparing nanosheet tungsten disulfide

    US20190194030A1